Α-Glucosidic hydroquinone derivatives from Viburnum erosum. (July 2021) - Park, Jinyoung; Lee, Jiho; Jang, Hyeon Seok; Jeong, Birang; Choi, Seong Yeon; Kim, Juyeol; Kwon, Yong Soo; Yang, Heejung
Abstract: Six undescribed compounds (1–6 ) were isolated from the leaves of Viburnum erosum along with four known compounds 7–10 . The structures were determined by NMR and MS spectroscopic analyses, and their absolute configurations were established by chemical and spectroscopic methods. Compounds 1 –6 were α -glucosidic hydroquinone derivatives with different linear monoterpenoid structures. Compounds 1–10 were also evaluated for their tyrosinase inhibitory activities, and 10 showed potent inhibition of tyrosinase enzyme with IC 50 value of 37.9 μ M compared to 47.6 μ M of the positive control ( β -arbutin). Graphical abstract: Image 1 Highlights: Six undescribed α-glucosidic hydroquinone derivatives were isolated from Viburnum erosum . Six undescribed compounds were structurally diversed by different linear monoterpenoid derivatives. The potent tyrosinase inhibition of V. erosum extract was gave arisen from (−)-epipinoresinol. The potent bioactive biflavonoid, amentoflavone, was found in high content.